Materializing digital futures touch, movement, sound and vision - Cinque, Toija ca. 20. Jh; Vincent, Jordan Beth ca. 20./21. Jh (Bloomsbury Academic, 2022)
"Digital, visual media are found in most aspects of everyday life, from workplaces to household devices – computer and digital television screens, appliances such as refrigerators and home assistants, and applications for social media and gaming. Each technologically enabled opportunity brings an increasingly sophisticated language with the act of pursuing the intrasensorial ways of perceiving the world around us – through touch, movement, sound and vision – that is the heart of screen media use and audience engagement with digital artifacts. Drawing on digital media’s currently evolving transformation and transforming capacity this book builds a story of the multiple processes in robotics and AI, virtual reality, creative image and sound production, the representation of data and creative practice. Issues around commodification, identity, identification, and political economy are critically examined for the emerging and affecting encounters and perceptions that are brought to bear."
Keywords: Digitalisierung; Neue Medien; Digital media / Social aspects; Multimedia communications / Social aspects; Human-computer interaction; Aufsatzsammlung